Cardiomyocyte-specific CYP2J2 and its therapeutic implications. (3rd August 2022) - Valencia, Robert; Bassiouni, Wesam; Darwesh, Ahmed M.; Bapuji, Raj; Seubert, John M.
ABSTRACT: Introduction: Cytochrome P450s (CYPs) are a superfamily of monooxygenases with diverse biological roles. CYP2J2 is an isozyme highly expressed in the heart where it metabolizes endogenous substrates such as N-3/N-6 polyunsaturated fatty acids (PUFA) to produce lipid mediators involved in homeostasis and cardioprotective responses. Expanding our knowledge of the role CYP2J2 has within the heart is important for understanding its impact on cardiac health and disease. Areas covered: The objective of this review was to assess the state of knowledge regarding cardiac CYP2J2. A literature search was conducted using PubMed-MEDLINE (from 2022 and earlier) to evaluate relevant studies regarding CYP2J2-mediated cardioprotection, small molecule modulators, effects of CYP2J2 substrates toward biologically relevant effects and implications of CYP2J2 polymorphisms and sexual dimorphism in the heart. Expert opinion: Cardiac CYP2J2-mediated metabolism of endogenous and exogenous substrates have been shown to impact cardiac function. Identifying individual factors, like sex and age, that affect CYP2J2 require further elucidation to better understand CYP2J2ʹs clinical relevance. Resolving the biological targets and activities of CYP2J2-derived PUFA metabolites will be necessary to safely target CYP2J2 and design novel analogues. Targeting CYP2J2 for therapeutic aims offers a potential novel approach to regulating cardiac homeostasis, drug metabolism and cardioprotection.